Short and Long Run Effects of Leniency Programs on Cartel Stability and Prosecution - Borrell, Joan Ramon; García, Carmen; Jiménez, Juan Luis; Ordóñez-de-Haro, José Manuel (Oxford University Press, 2024)
This study investigates the effects of leniency programs on cartel duration, cartel fines, and the length of investigations, providing empirical insights that contribute to the ongoing debate regarding their theoretical and empirical implications. The introduction of leniency programs in two different jurisdictions (EU and Spain) at different times and the exogeneity of the introduction date enable us to identify their impact using difference-in-differences estimations. We empirically show that leniency programs, by destabilizing existing cartels, allow for the detection of the longer-lasting ones in the short run. In the long run, our results suggest that destabilization effects prevail, and leniency programs discourage the creation of new cartels. Specifically, our findings indicate that the duration of detected cartels almost doubles in the short run and nearly halves in the long run. Finally, our study reveals that the introduction of leniency programs results in a significant increase in the average fines per cartel case, both before and after taking into account the fine reductions resulting from these programs. This suggests that leniency programs contribute to stronger sanctions against cartels, enhancing their general deterrent effect. However, our findings also indicate that leniency programs lengthen the average duration of cartel investigations, which may hinder the ability of competition authorities to proactively pursue other cases.
Keywords: Delincuencia; Antitrust; Competition Policy; Cartels; Leniency Programs